Relationships between internal and external training load demands and match load demands in elite women volleyball players - Altundag, E.; Akyildiz, Z.; Lima, R.; de Oliveira Castro, H.; Çene, E.; Akarçesme, C.; Miale, G.; Clemente, F. M. (Proceedings of the Institution of Mechanical Engineers, Part P: Journal of Sports Engineering and Technology, 2025)
This study investigates the relationships between the internal and external load demands imposed on elite female volleyball players during training and matches. Fourteen elite female world champion volleyball league players participated in this study (mean ± standard deviation (SD); age, 22 ± 0.9 years; height, 195.1 ± 7.6 cm; body mass, 71.4 ± 6.3 kg). The research lasted for 10 months. Moderate positive relationships were found between match load and training load (r = 0.48) and between high metabolic load distance (HMLD) in matches and HMLD in training (r = 0.56). There were also strong positive relationships between local positioning system (LPS) recorded jumps in matches and during training (0.61), accelerations in matches and during training (r = 0.72), and decelerations in matches and during training (r = 0.68). A weak positive relationship was reported between training accelerations/decelerations and match accelerations/decelerations (r = 0.28). The relationships between accelerations and decelerations in matches (r = 0.92) and between accelerations and decelerations during training (r = 0.90) were very strong. As a result, it is concluded that as the load, HMLD, jumps, accelerations, and decelerations values obtained during training increase, the values obtained in competitions also increase. The results of this study can help sports scientists and coaches understand the relationships between training and competition data obtained from electronic tracking devices.